PENERAPAN KEGIATAN BERKEBUN DALAM MENINGKATKAN KETERAMPILAN PROSES SAINS ANAK TAMAN KANAK-KANAK (Quasi Eksperimen pada Kelompok B di TK Kartika Siliwangi XIX-I dan TK Pelita Bunda Bandung Tahun Ajaran 2017-2018) - Demas Mira Mawaddah; Asep Deni Gustiana; Dewi Tri Jayanti (UPI Kampus Cibiru, 2019)
Abstract: Study aims to determine the effectiveness of methods with gardening activities to the skills of early childhood science process. The method used is Quasi Eksperimen with the design of the Nonequivalent Control Group Design study. This research was conducted on group B in Kartika Siliwangi XIX-I Kindergarten and Pelita Bunda Gegerkalong Kindergarten Bandung with 15 experimental group and 15 control group. The research data was obtained using research instrument in the form of non-formal interview and observation guidance of science process skill of children aged 5-6 years. Based on the results of the research, the initial conditions in the experimental group showed that children with low science process skills were 67%, while in the control group were 60%. Implementation of science learning using gardening activities in improving the science process skills of kindergarten children group B developed well. This can be seen from the results of the study on the learning process recorded for the experimental group as much as 97% and in the control group as much as 85%. Recommendations submitted to Kindergarten Teachers who will conduct science-based learning of the science process should be created a whole learning scenario that illustrates clear instructions on the steps of children's learning activities sequentially from beginning to end. For the next researcher, the result of this research can be used as the starting point to develop the learning process of children science skill of kindergarten, and for the school party, it is better to start using learning science process skill in school by adding media that can support learning, facilities and infrastructure to support the success of process skill science in school.Keywords: Skills Process of Science, Gardening Activities, Kindergarten Children